Informal communications in the conditions of the Russian-Ukrainian war - Olga Yurkova; Lydiya Smola; Valerie Kasianchuk (Social Sciences and Humanities Open, 2025)
Using the onset of Russia's full-scale invasion of Ukraine as a reference point, we analyze informal communications on social media. Drawing on 670 rumors circulated in Ukraine's information space between February 24, 2022, and December 31, 2023, we focus on the most frequently used platforms – Telegram and Facebook, with Viber to a lesser extent. We examine the emotional coloring of these rumors (Knapp, 1944), their temporal dynamics, patterns of dissemination, and their life cycles within Ukraine's information space during this period.We discovered that shifts in the dominant emotional coloring of rumors partially correlate with changes in the psychological state of Ukrainian society (Zlobina, 2023). We propose redefining the starting point of a rumor's life cycle: not as the moment it begins circulating but as the event that triggers public interest or information-seeking behavior. Furthermore, we recommend treating the dissemination of refutations or corrections as an integral part of the rumor's life cycle.